Effects of Climatic Conditions on Bovine Semen Characteristics - Zuzana Biniová; Jaromír Ducháček; Luděk Stádník; Martina Doležalová; Radim Hájek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2017)
The present study assessed the effects of climatic conditions and year‑period (month) on both qualitative and quantitative characteristics of bovine semen in Czech Republic. The semen was collected twice a week using artificial vagina at artificial insemination center Hradištko in period 2011 – 2013. The effects of collection month, average daily ambient temperature and average daily relative humidity on volume, sperm concentration and progressive motility above head of collected semen and also on number of produced artificial insemination straws of required quality were analyzed using statistical analysis (procedures: UNIVARIATE, STEPWISE, GLM) in software SAS 9.3 (SAS/STAT® 9.3, 2011). Collection month, average daily ambient temperature, average daily relative humidity, and breed had a significant effect (P < 0.05) on all evaluated characteristics. The maximum values of motility and sperm concentration were found in March and in April. The highest volume of collected semen was found in July and in September and the lowest in November, when also the lowest number of straws was produced. Motility and sperm concentration were significantly influenced by average daily ambient temperature and average daily relative humidity, where the maximum values were recorded in average daily ambient temperature over 14.85 °C and average daily relative humidity over 72.05 %. The results are important to the management of artificial insemination center responsible for planning of semen collection, processing and artificial insemination straws production.